Analisis Perilaku Dan Kecerdasan Konsumen Terhadap Konsumsi Produk Kosmetik Kecantikan - Anggraini, Adelia Septina Ika; Elnanda Putri Jayanti; Farah Imelda Wichdati; Wihdatul Hasana; Novia Restu Windayani (Universitas Negeri Jakarta, 2023)
Cosmetics have become a basic human need. Obtaining cosmetics requires purchasing for consumption, and consumers differ in their consumption behavior and intelligence. This influence on consumer behavior is crucial for studying and understanding, as it serves as a fundamental foundation for successful marketing strategy development, sales operations, consumer segmentation, and more focused and targeted buyer targeting. This study aims to determine consumer behavior and intelligence related to cosmetic product consumption, categorized by gender, occupation, and age. The data collection technique used in this study was a survey with a questionnaire. Primary data was obtained from questionnaire responses, while secondary data was sourced from literature in the form of books and scientific journal articles. The data collection process was carried out by distributing a questionnaire via a Google Form to the participants online. The instrument consisted of seventeen questions that had to be answered by the research object. The results of the study were related to consumer behavior and understanding of the variables used as instruments in data collection. Based on age range, each consumer exhibits different behaviors and levels of intelligence in using cosmetics according to their conditions and needs; therefore, there are variations in how beauty cosmetic products are consumed.